OPTIMALISASI PENGGUNAAN TRICHOKOMPOS TANDAN KOSONG SAWIT DAN PUPUK ORGANIK CAIR UNTUK MENINGKATKAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L) - Vonny Indah Sari; Neng Susi (Jurnal Agro Indragiri, 2026)
Mung beans are one of the important Leguminosae plants in Indonesia, ranking third after soybeans and peanuts. Green bean farming in Riau Province still faces challenges in soil fertility due to the presence of Ultisol (PMK) soil, which has low organic matter, low nutrient content, and is acidic in nature. Fertilization is one of the methods that can be used to improve soil fertility. Trichocompost is an organic compost fertilizer made from organic materials and contains the antagonistic fungus Trichoderma sp., which functions as a decomposer of organic materials. Along with the development of agricultural technology, natural liquid organic fertilizers have also been developed, which can be used to help overcome agricultural production obstacles. Liquid organic fertilizer is a solution resulting from the decomposition of organic materials derived from plant residues, animal manure, and human waste, containing more than one essential nutrient. The use of organic fertilizers, both solid and liquid, reduces the use of inorganic fertilizers, thereby helping the soil to revitalize its ability as a fertile growing medium, which is expected to support a sustainable agricultural system. The research results showed that trichocompost and liquid organic fertilizers had a significant impact on all observation parameters, namely plant height, number of productive branches, flowering age, number of pods per plant, wet weight of seeds per plot, dry weight of seeds per plot, weight of 100 seeds, and root volume of mung bean plants. The best results were obtained using Trichocompost fertilizer and Supermas with doses of 90 kg/plot and 3 cc/l, respectively